SPE Annual Technical Conference and Exhibition 1989
DOI: 10.2118/19783-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Waterflood Infill Drilling in West Texas Clearfork and San Andres Carbonate Reservoirs

Abstract: In this paper we present the results of a technical and an economic evaluation of waterflood infill drillings in fourteen Clearfork and eleven San Andres carbonate reservoirs in West Texas. The initial waterflood recovery efficiency and the infill drilling waterflood recovery efficiency were estimated from decline curve analyses. The economic analysis was performed to evaluate the relative profitability of the waterflood infill drilling operations. For Clearfork units, the estimated initial wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The existence of different rock types with various thicknesses between two wells in a reservoir may cause a complex flow behavior. One of the applications of infill wells is to reduce the distance between the wells which helps maintain layer continuity and enhances well connectivity (Wu et al 1989;Malik et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of different rock types with various thicknesses between two wells in a reservoir may cause a complex flow behavior. One of the applications of infill wells is to reduce the distance between the wells which helps maintain layer continuity and enhances well connectivity (Wu et al 1989;Malik et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that infill drilling can improve the recovery of hydrocarbons by accelerating hydrocarbon production because most reservoirs in the world are not homogeneous (1)(2)(3)(4)(5)(6)(7) . Driscoll (1) , Gould and Munoz (2) and Gould and Sarem (4) summarized the various factors that contribute to increased recovery after infill drilling:…”
Section: Introductionmentioning
confidence: 99%
“…The infill drill wells reduce the well spacing of the hydrocarbon fields and then enhance the well connectivity. Wu et al (7) reported the results of their study to determine the impact of infill drilling on waterflood recovery in a West Texas carbonate reservoir. Their study shows a certain degree of correlation between waterflood recovery and well spacing.…”
Section: Introductionmentioning
confidence: 99%